2021
DOI: 10.1039/d0cc05218c
|View full text |Cite|
|
Sign up to set email alerts
|

EPR imaging of sinapyl alcohol and its application to the study of plant cell wall lignification

Abstract: Bioorthogonal chemical reporter strategy can be successfully combined with EPR spectroscopy in plant tissues to detect the incorporation of a tagged monolignol into the lignin polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Surprisingly the H‐tetrazine 8 showed little turn‐on in PBS. It has previously been suggested that H‐tetrazines can be too unstable to be used in biological applications, [55] and upon stability assessment of our tetrazine library in PBS (Figure S3A) it is clear that 8 is somewhat prone to degradation over time. Thereby the reaction between 1 and 8 cannot go to completion because of competition with hydrolytic degradation and unquenching of the H‐tetrazine.…”
Section: Resultsmentioning
confidence: 72%
“…Surprisingly the H‐tetrazine 8 showed little turn‐on in PBS. It has previously been suggested that H‐tetrazines can be too unstable to be used in biological applications, [55] and upon stability assessment of our tetrazine library in PBS (Figure S3A) it is clear that 8 is somewhat prone to degradation over time. Thereby the reaction between 1 and 8 cannot go to completion because of competition with hydrolytic degradation and unquenching of the H‐tetrazine.…”
Section: Resultsmentioning
confidence: 72%
“…8–10 Biorthogonal methods were recently applied to elucidate the lignification kinetics of plant cell walls since lignin cannot be observed in vivo through gene labeling like proteins. 11–13…”
mentioning
confidence: 99%
“…[8][9][10] Biorthogonal methods were recently applied to elucidate the lignification kinetics of plant cell walls since lignin cannot be observed in vivo through gene labeling like proteins. [11][12][13] In 2011, Tobimatsu and his coworkers designed and synthesized two new fluorescent labeled lignin precursor monomers, CADMAC (dimethylaminocoumarin tagged coniferyl alcohol) and CANBD (nitrobenzofuran tagged coniferyl alcohol). 14 Copolymerization was carried out in vitro with horseradish peroxidase, and the complexation was monitored in real time.…”
mentioning
confidence: 99%